A second order sliding power control & resonant filtering approach to mitigate grid unbalance effects on a DOIG wind energy based system - Valenciaga, Fernando (2017)
This paper presents a multivariable power control design applied to a DFIG Wind Energy Conversion based System (WECS). The multiple control objectives pursued in this work include not only tracking temporal profiles of active and reactive power grid injection but also regulate some important internal variables like the DC bus voltage. To fulfil these targets a multivariable control scheme is developed following second order sliding mode techniques. This theoretical framework allows synthesizing controllers with attractive features like finite time convergence, robustness against external perturbations and unmodeled dynamics, simple implementation, etc. To endorse the control system with grid support features under voltage unbalances the multivariable SOSM controller is combined with a set of resonant filters. This mixed scheme allows to substantially reduce the oscillations of simple and double grid frequency on the electric torque and the power injected into the grid. The overall performance of this control proposal is evaluated using representative simulations.